The Impact of the Disclosure in the Annual Report on the Decisions of Investors of Listed Companies in the Stock Exchange of Thailand - Sincharoonsak, Titaporn (Asian Interdisciplinary and Sustainability Review, 2019)
This research aims to examine the impact of the disclosure in the annual report with regards to the abnormal returns and the cumulative abnormal returns of the companies listed in the Stock Exchange of Thailand. The sample for this research are 230 of the listed companies in the Stock Exchange of Thailand between the year 2013 and 2017. Adopted in the data analysis are the Chow test for the analysis on split data sets and the multiple regression analysis. The analysis of the data set split into a group containing companies with low book value per share and the other group containing companies with high book value per share finds that the auditor’s report, the investment in subsidiaries and associated companies, the corporate governance, the current ratio, the quick ratio, the operating profit margin, the return on asset ratio, the return on equity ratio, the interest coverage ratio, the dividend payout ratio, the debt to equity ratio affect the abnormal returns and the cumulative abnormal returns in different ways. It is also found that the relationship between the information disclosed in the annual report, the abnormal returns as well as the cumulative abnormal returns, and the consequent decisions of investors differs between firms with high book value per share and those with low book value per share.